Sy nthesis of Some New Schifrs-Bases Derived From 2-(4-m ethoxy phenyl)-5- (4-amino phenyl)-1,3,4-0xadiazole - Tomma, J. H (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A new compound 2-(4-methoxyphcnyl)-5-(4-aminophenyl)-1,3,4- oxadiazole (VI) was prepared by intramol ecular condensation reaction followed by elimination of some simple moieties such as IhO and HCI by using POCI3 with acid hydrazide. A series of new ShiffsÂ bases 2-(4-methoxyphenyl)-5-[4(4:alkoxybenzoyloxy) benzylidene amino phenyl] I,3,4-oxadia:t.ole (VII].was synthesized from treatment of oxadiazole derivative [VI] with an appropriate aromatic aldehyde (IU). Structof the resulting products have been ascertaim:d by their melting pointS, elemental analysis ( some of them) and spectral data.